2014
DOI: 10.1007/s00213-014-3842-5
|View full text |Cite
|
Sign up to set email alerts
|

Glucose, relational memory, and the hippocampus

Abstract: The discussion considers the cognitive processes and hippocampal basis for paired associate learning and retention and the implications for glucose's mode of action. It is proposed that glucose during encoding serves to make the delayed memories initially more available, whereas its influence during delayed retrieval makes available memories temporarily more accessible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…colour-location) bindings would determine whether glucose operates selectively on tasks with a spatial component or more generally on binding processes. This is important because the hippocampal system supports a wide range of binding processes (Olsen et al 2012 ) and while there is some evidence that glucose does not enhance the short-term maintenance of non-spatial (word-word) bindings (Stollery and Christian 2015 ), it would seem prudent to establish the proposed role of spatial memory in the observed enhancement. Thus, the possibility that spatial processing is an important feature of binding tasks that show short-term enhancement due to glucose remains to be determined.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…colour-location) bindings would determine whether glucose operates selectively on tasks with a spatial component or more generally on binding processes. This is important because the hippocampal system supports a wide range of binding processes (Olsen et al 2012 ) and while there is some evidence that glucose does not enhance the short-term maintenance of non-spatial (word-word) bindings (Stollery and Christian 2015 ), it would seem prudent to establish the proposed role of spatial memory in the observed enhancement. Thus, the possibility that spatial processing is an important feature of binding tasks that show short-term enhancement due to glucose remains to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…McNay and Gold 2001 ; Riby and Riby 2006 ; Winocur 1995 ), only a few human studies have undertaken a focussed evaluation of hippocampal-based cognitive tasks to explore this (e.g. Stollery and Christian 2015 ).…”
mentioning
confidence: 99%
“…3). Logical memory is known to be used for the assessment of verbal declarative memory (Hori et al, 2013; Muller et al, 2007a; Perry and Hodges, 2000), whereas visual paired associates have been used to assess visual declarative memory (Kessels et al, 2011; Papalambros et al, 2017; Stollery and Christian, 2015). Declarative memory is mediated by the circuitry involving bidirectional connections between the neocortex, the parahippocampal region, and the hippocampus (Eichenbaum, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that hyperglycemia in T2DM plays an important role in the development of cognitive dysfunction pointing to the conceivable impairment in the hippocampus which is an important anatomical basis and nerve center for learning, memory, and spatial orientation in the human brain. 14 Numerous clinical and fundamental studies have demonstrated discovery of cognition and memory dysfunction in both T1D and T2D, but the pathogenesis remains unclear. 15 In this study, we aimed to validate the hypothesis that GF is a more critical factor that would promote the neuron apoptosis and impaired hippocampus function than continuous hyperglycemia using an idiopathic T2DM animal model for the first time.…”
Section: Introductionmentioning
confidence: 99%